Study on Conventional and Rheological Properties of Corn Stalk Bioasphalt/PPA Composite Modified Asphalt - Fuhai Wang (Hindawi Limited, 2021)
As a new type of pavement material, bioasphalt has received more and more attention. However, the high-temperature behavior of bioasphalt is poor after blending with asphalt binder. In order to solve this problem and facilitate the waste utilization and resource conservation, the corn stalk bioasphalt/PPA composite modified asphalt was proposed. The conventional performance tests and rheological tests were conducted to evaluate high-temperature and low-temperature behavior. Fourier transform infrared reflection (FTIR) test was undertaken to analyze the mechanism of modified asphalt. The results indicated that blended asphalt penetration and ductility gradually decrease with the PPA content increasing. The softening point and viscosity of the modified asphalt increased, which led to an improvement of blended asphalt’s rigidity. The PPA increased the rutting index of corn stalk bioasphalt/PPA composite modified asphalt. However, bioasphalt had a negative effect on its high-temperature performance. The corn stalk bioasphalt/PPA composite modified asphalt could meet the specification requirement at −18°C considering the creep rate and stiffness modulus, indicating it had outstanding crack resistance. When the PPA and bioasphalt respect to the weight of neat asphalt were 6%–8% and 10%–16%, respectively, the corn stalk bioasphalt/PPA composite modified asphalt performance was optimal. However, shear time and shear rate merely affected the proposed modified asphalt performance. The bioasphalt did not affect the chemical structure of asphalt. However, PPA generated new functional groups (P-O single bond, phosphate (RO)3P = O, and P=O double bond) causing a chemical modification in the asphalt binder. This study can provide a basis for applying bioasphalt, making road engineering more economical and environmentally friendly.